2020
DOI: 10.3390/ijerph17030941
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Periphyton Microbial Growth, Activity, and Pollutant Removal Efficiency to Cu Exposure

Abstract: Periphyton is an effective matrix for the removal of pollutants in wastewater and has been considered a promising method of bioremediation. However, it still needs to be verified whether periphyton can maintain microbial activity and pollutant removal efficiency when dealing with the influence with complex components, and the underlying mechanisms of periphyton need to be revealed further. Herein, this study investigated the microbial growth, activity and functional responses of periphyton after removal of Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…De Lorenzo (2008) provides a newer approach of bioremediation with the help of algal species. Periphytons inhabit the surface waters and are an important factor in determining the primary productivity of aquatic ecosystem (Zhong et al, 2020). The components of periphyton are algae, diatoms, fungi, bacteria, protozoa as well as small multicellular animals, and organic detritus (Wu et al, 2014).…”
Section: Bioremediation By Periphytonmentioning
confidence: 99%
“…De Lorenzo (2008) provides a newer approach of bioremediation with the help of algal species. Periphytons inhabit the surface waters and are an important factor in determining the primary productivity of aquatic ecosystem (Zhong et al, 2020). The components of periphyton are algae, diatoms, fungi, bacteria, protozoa as well as small multicellular animals, and organic detritus (Wu et al, 2014).…”
Section: Bioremediation By Periphytonmentioning
confidence: 99%
“…Additionally, Lu et al (2020) observed that periphytic biofilms significantly reduce Cd accumulation in rice, with a Cd adsorption rate of 390 pmol cm −2 s −1 [10]. Furthermore, when applied in wastewater treatment, periphytic biofilms have exhibited a high tolerance to Cu concentrations exceeding 2 mg L −1 [11]. By absorbing and accumulating Cd and Pi, periphytic biofilms effectively remove these contaminants from the water, reducing their availability to other organisms [12].…”
Section: Introductionmentioning
confidence: 99%